2022
DOI: 10.1038/s41598-022-15286-4
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly approach to improve traits of winter wheat by combining cold plasma treatments and carbonization of subtropical biomass waste

Abstract: This study aims to improve the quality and quantity of winter wheat by using the potential of combining the use of cold plasma and waste biorefinery products for improving wheat yield. Plasma was applied by a radio frequency (RF) plasma reactor operated with air for 180 s and 50 W. The waste biorefinery products, including pyroligneous acid, biochar, and azolla compost, were used as plant nutrition. The effects of cold plasma treatment and waste biorefinery products were determined by measuring plant photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…It is believed that protein concentration is an important indicator of the metabolism status. In line with our findings, employing non‐thermal plasma was accompanied by an increase in photosynthesis efficiency, [ 23–25 ] proline, [ 26 ] and protein. [ 27 ] Besides, the plasma‐associated augmentation in the concentration of tropane alkaloids and phenols (phenylpropanoid‐derivatives), as well as upregulation in the PAL activity refer to the high efficacy of plasma to act as an elicitor toward inducing secondary metabolism and defense system.…”
Section: Discussionsupporting
confidence: 91%
“…It is believed that protein concentration is an important indicator of the metabolism status. In line with our findings, employing non‐thermal plasma was accompanied by an increase in photosynthesis efficiency, [ 23–25 ] proline, [ 26 ] and protein. [ 27 ] Besides, the plasma‐associated augmentation in the concentration of tropane alkaloids and phenols (phenylpropanoid‐derivatives), as well as upregulation in the PAL activity refer to the high efficacy of plasma to act as an elicitor toward inducing secondary metabolism and defense system.…”
Section: Discussionsupporting
confidence: 91%
“…Plasma provides a comprehensive environment for optical, electrical, magnetic and active particles 12 . It is widely used in botany, and plasma technology can reduce crop seed pollution, improve the storage quality of fruits and vegetables, promote seed germination, improve seed vigour, and increase crop yields 13–17 . Chou et al 18 suggested that plasma treatment can promote the germination rate of plant seeds and seedling growth.…”
Section: Instructionmentioning
confidence: 99%
“…12 It is widely used in botany, and plasma technology can reduce crop seed pollution, improve the storage quality of fruits and vegetables, promote seed germination, improve seed vigour, and increase crop yields. [13][14][15][16][17] Chou et al 18 suggested that plasma treatment can promote the germination rate of plant seeds and seedling growth. It has been reported to have the potential to improve the biomass and edible quality of soybean sprouts.…”
mentioning
confidence: 99%